2007
DOI: 10.1111/j.1365-2729.2007.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

How students and instructors using a virtual learning environment perceive the fit between technology and task

Abstract: Virtual learning environments (VLEs) are widespread in higher education today, typically used to deliver instructional materials and facilitate communication within a course. This study aimed to investigate the task-technology fit of VLEs for their two main groups of users: instructors and students, using the VLE WebCT. Task-technology fit, user satisfaction, attitude towards use and anticipated consequences of use were found to be significantly higher for students than for instructors. Instructors were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 48 publications
5
62
0
1
Order By: Relevance
“…The proposed research model is in accordance with past efforts that integrated TTF, ECM, and individual learning support (e.g., McGill & Hobbs, 2008;Lin, & Wang, CH., 2012;Cheng, 2014). The study's hypotheses are highlighted in the research model.…”
Section: Research Model and Hypothesesmentioning
confidence: 50%
“…The proposed research model is in accordance with past efforts that integrated TTF, ECM, and individual learning support (e.g., McGill & Hobbs, 2008;Lin, & Wang, CH., 2012;Cheng, 2014). The study's hypotheses are highlighted in the research model.…”
Section: Research Model and Hypothesesmentioning
confidence: 50%
“…The reported satisfaction rating results presented here support their findings. McGill & Hobbs (2008) also noted the anecdotal evidence that students, being generally younger than staff, appear to have a greater comfort with technology, and hence they also hypothesized that students would, and also found that students did, report a more positive attitude towards OLE use. Generally, the reported importance rating results presented here also support their findings.…”
Section: Importance-satisfaction Analysismentioning
confidence: 99%
“…Although Table 6 shows that not all of the observed differences between student and staff mean ratings are statistically significant, there is a measure of coherence in the alignment of the lines, especially in 2004 (Figure 1). McGill & Hobbs (2008), noting the dual (end user and designer) and more complex (compared to students) role played by academic staff when operating in an OLE, and also prior research indicating a negative link between task complexity and user satisfaction, hypothesized that staff would, and found that staff did, report a lower satisfaction than students when using an OLE. The reported satisfaction rating results presented here support their findings.…”
Section: Importance-satisfaction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Meglepő egy olyan tanulmány eredménye, amely arról számol be, hogy a tanárok kevésbé voltak elégedettek az általuk létrehozott tanulási környezettel, mint tanulóik (McGill és Hobbs, 2008). Egy másik publikáció tanárokkal és hallgatókkal folytatott interjú alapján szintén arra a következtetésre jutott, hogy a hallgatók sokkal pozitívabban viszonyultak a tanulási környezetekhez, mint a tanárok (Heaton-Shrestha, 2009).…”
Section: Pajo éS Wallaceunclassified